Mandibular distraction to correct severe non-isolated mandibular hypoplasia: The role of drug-induced sleep endoscopy (DISE) in decision making. (January 2022) - van der Plas, Pleun P.J.M.; Joosten, Koen F.M.; Wolvius, Eppo B.; Koudstaal, Maarten J.; Mathijssen, Irene M.J.; van Dooren, Marieke F.; Pullens, Bas
Abstract: Objectives: In patients with mandibular hypoplasia, mandibular distraction osteogenesis (MDO) aims to relieve tongue-based airway obstruction. Drug-induced sleep endoscopy (DISE) provides a dynamic assessment of the upper airway and visualizes anatomical site and cause of airway obstruction. The aim of this study was to evaluate the effect of MDO on tongue-based airway obstruction found by DISE within a non-isolated patient population with severe upper airway obstruction (UAO). Furthermore, we aimed to assess the additional value of DISE in clinical decision making by correlating DISE findings to functional airway outcomes after MDO. Methods: Findings on DISE in children who underwent MDO were retrospectively gathered and evaluated. According to DISE findings, severity of tongue-based obstruction was scored using a 4-step classification similar to the one that is used by Bravo et al.. Intubation conditions were scored according to the Cormack Lehane score (CLS). Pre-and postoperative DISE findings were compared and correlated with functional airway outcomes following MDO. Results: In 19 out of 28 MDO procedures, both a pre-and postoperative DISE was available. Tongue-based obstruction scores improved in 13 procedures, which correlated to a functional improvement in seven. Postoperative tongue-based obstruction differed significantly between patients with successful MDO and patients treated unsuccessfully (2.00 ((Interquartile range (IQR) 1.00–2.00) vs. 3.00 (IQR 2.00–4.00), p = 0.028), whereas this difference was not significant for the CLS (1.00 (IQR 1.00–1.50) vs. 2.00 (IQR 1.00–4.00), p = 0.066). If no improvement of tongue-based obstruction was seen, MDO is very unlikely to be successful on the functional airway. Conclusions: DISE provides information on the site and nature of airway obstruction and can visualize the effect of MDO on the severity of tongue-based airway obstruction. Therefore, it can be of additional value in understanding the differences in functional airway outcomes after MDO and aids in deciding appropriate and targeted treatment. Hence, standardized use of DISE, in addition to the clinical assessment of mandibular position and a polysomnography, during MDO management is highly recommended. Highlights: Sleep endoscopy is valuable in evaluating effectiveness of mandibular distraction. Improvement of tongue-based airway does not guarantee successful clinical outcome. Mandibular distraction does not always result in an improved oropharyngeal airway. Sleep endoscopy performance during mandibular distraction is highly recommended.